2014
DOI: 10.1007/s10802-014-9918-1
|View full text |Cite|
|
Sign up to set email alerts
|

Self-Reported and Observed Punitive Parenting Prospectively Predicts Increased Error-Related Brain Activity in Six-Year-Old Children

Abstract: The error-related negativity (ERN) is a negative deflection in the event-related potential (ERP) occurring approximately 50 ms after error commission at fronto-central electrode sites and is thought to reflect the activation of a generic error monitoring system. Several studies have reported an increased ERN in clinically anxious children, and suggest that anxious children are more sensitive to error commission—although the mechanisms underlying this association are not clear. We have previously found that pun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 85 publications
11
63
0
Order By: Relevance
“…Prevention of social anxiety for those at risk might be improved by targeting factors that influence the link between early BI and later hypersensitivity toward errors; parenting is one promising factor that may influence this relation. 43,44 Conversely, in adolescents already diagnosed with social anxiety or expressing symptoms, improved treatment might target error preoccupation, as opposed to hypersensitivity toward errors. Consistent with this notion, intervention studies have shown that treatment for anxiety disorders does not influence the ERN itself.…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of social anxiety for those at risk might be improved by targeting factors that influence the link between early BI and later hypersensitivity toward errors; parenting is one promising factor that may influence this relation. 43,44 Conversely, in adolescents already diagnosed with social anxiety or expressing symptoms, improved treatment might target error preoccupation, as opposed to hypersensitivity toward errors. Consistent with this notion, intervention studies have shown that treatment for anxiety disorders does not influence the ERN itself.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced error-related negativity has been associated with high sensitivity to punishment and hypervigilance (15) and is typical for common comorbidities of childhood maltreatment, including depression and anxiety (16). It is further suggested that environmental adversity and punitive parental behavior, which are often considered etiological factors for various internalizing disorders, may be linked to increases in error-related negativity, which are associated with these disorders (17).…”
Section: Discussionmentioning
confidence: 99%
“…Maltreated individuals also tend to avoid threat (19) and exhibit heightened neural reactivity to threat-related faces (20)(21)(22); furthermore, their hypersensitivity to punishment is associated with increased risk taking to avoid potential punishments (23). Thus, given that punishment and punitive parenting lead to lasting enhanced error-related negativity (17,24), persistent harsh punishment experiences in childhood may sensitize the abused child to errors and lead to an overactive error-monitoring system.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using Event Related Potentials (ERPs), which measure electrical potentials to isolate quickly-occurring (i.e., on the order of milliseconds) neural processes in response to specific events (e.g., self-monitoring following a button-press response), and functional Magnetic Resonance Imaging ( f MRI), a measure of the hemodynamic response that measures activation in specific neural structures, have shown that more harsh parenting is linked to hyperactivation of the amygdala (Taylor, Eisenberger, Saxbe, Lehman, & Lieberman, 2006), and increased sensitivity to errors, (Brooker & Buss, 2014; Meyer et al, 2015), both of which indicate dysregulation and enhanced risk for anxiety problems during childhood. High rates of sensitive parenting, on the other hand, are linked to the healthy development of the corpus callosum, a brain region associated with high order self-regulation (Ghassabian et al, 2013; Kok et al, 2013).…”
Section: Introductionmentioning
confidence: 99%